Safe bearing capacity evaluation of the bridge site along Syafrubesi-Rasuwagadhi road, Central Nepal - Manandhar, Suman; Shrestha, Uttam Bol; Yasufuku, Noriyuki; Omine, Kiyoshi; Kobayashi, Taizo (Bulletin of the Department of Geology, 2009)
The research work was carried out at the proposed bridge site along Syafrubesi-Rasuwagadhi Road, Central Nepal. The study was based on field SPT/DCPT and laboratory tests. N values were determined from SPT/DCPT test. The index and mechanical properties of granular soils were computed in laboratory. Then, ultimate and allowable bearing capacities with safety factor 3 for maximum tolerable limit of 40 mm settlement was estimated by empirical equations provided by Teng (1988) and Terzaghi and Peck (1978). It is recommended that safe bearing capacity for 6 m size open square foundation at left and right abutments are suitable within 4.5 to 6 m depth.   doi: 10.3126/bdg.v12i0.2254 Bulletin of the Department of Geology, Vol. 12, 2009, pp. 95-100